An iterative algorithm based on the generalized viscosity explicit methods for an infinite family of accretive operators - Sow, Thierno (Armenian Journal of Mathematics, 2022)
In this paper, we introduce and study a new iterative method based on the generalized viscosity explicit methods (GVEM) for solving the inclusion problem with an infinite family of multivalued accretive operators in real Banach spaces. Applications to equilibrium and to convex minimization problems involving an infinite family of semi-continuous and convex functions are included. Our results improve important recent results.